2001
DOI: 10.1034/j.1600-0749.2001.140203.x
|View full text |Cite
|
Sign up to set email alerts
|

The Mouse p (pink‐eyed dilution) and Human P Genes, Oculocutaneous Albinism Type 2 (OCA2), and Melanosomal pH

Abstract: Recessive mutations of the mouse p (pink-eyed dilution) gene lead to hypopigmentation of the eyes, skin, and fur. Mice lacking a functional p protein have pink eyes and light gray fur (if non-agouti) or cream-colored fur (if agouti). The human orthologue is the P protein. Humans lacking a functional P protein have oculocutaneous albinism type 2 (OCA2). Melanocytes from p-deficient mice or OCA2 individuals contain small, minimally pigmented melanosomes. The mouse and human proteins are predicted to have 12 memb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
123
1
4

Year Published

2002
2002
2010
2010

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(130 citation statements)
references
References 86 publications
(149 reference statements)
2
123
1
4
Order By: Relevance
“…(Figure 4). 15 OCA2 albinism in Polynesia HC Johanson et al identified in these individuals, although they were not sequenced across all exons for this study. One Australian Caucasian with OCA was found to be a compound heterozygote for one novel apparent pathological missense mutation b.1185G4T, OCA2 p.Met395Ile and one common hypopigmentation-related allele b.1327G4A, p.Val443Ile.…”
Section: Oca2 Gene Mutation Detectionmentioning
confidence: 99%
See 2 more Smart Citations
“…(Figure 4). 15 OCA2 albinism in Polynesia HC Johanson et al identified in these individuals, although they were not sequenced across all exons for this study. One Australian Caucasian with OCA was found to be a compound heterozygote for one novel apparent pathological missense mutation b.1185G4T, OCA2 p.Met395Ile and one common hypopigmentation-related allele b.1327G4A, p.Val443Ile.…”
Section: Oca2 Gene Mutation Detectionmentioning
confidence: 99%
“…Structurally, the 838 amino-acid P-protein is predicted to contain 12 transmembrane-spanning domains. The cDNA is encoded in 24 exons, 14,15 and the locus covers over 345 kb. 16 Though initially reported as an integral melanosomal protein potentially associated with transport of some molecule into the melanosome, its subcellular localization has been a subject of debate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, other investigators have reached opposite conclusions. Puri et al (Puri et al, 2000) proposed that the pH of melanosomes in p-null melanocytes is not acidic, whereas an acidic melanosomal environment is important for melanin synthesis (Brilliant, 2001). However, the use of tyrosinaserelated protein 1 (Tyrp1), a Tyr family protein that shares 43% amino acid sequence identity with Tyr (Vijayasaradhi et al, 1995), as a melanosomal marker in p-null melanocytes may be inappropriate because Tyrp1, like Tyr, is mislocalized in the absence of p .…”
Section: Introductionmentioning
confidence: 99%
“…In mice and humans where the P protein is nonfunctional, albinism occurs, indicating its crucial role in pigmentation. 13,14 The gene located 11.7 kb from HERC2 requires 345 kb, but it requires only 24 exons to produce a 110 kDa protein with 838 residues. These two seemingly unrelated genes have a major effect on eye color in humans.…”
Section: Introductionmentioning
confidence: 99%